Teacher Beliefs and Perspectives of Practice: Impacts of Online Professional Learning - Jessica Hunt; Alejandra Duarte; Brittany Miller; Brianna Bentley; Laura Albrecht; Lance Kruse (MDPI AG, 2023)
Efforts to improve teachers' knowledge of tools and strategies are often intertwined with their beliefs regarding mathematics teaching and learning. Yet, few studies have examined the impact of professional development designed to bolster teachers' knowledge of and beliefs about young children's mathematical development. In this study, we evaluated whether participants' beliefs changed significantly after engaging in online professional learning on teaching math to young children, overall orientations of participants' teaching practices and shifts over time, and how changed beliefs might coincide with changed orientations to practice. We employed a multilevel mixed methods design, with quantitative results showing changes in participants' overall beliefs based on survey data. We discuss how trends in perceived instructional practices coincide with beliefs found to be statistically significant in the quantitative analysis and the potential for online professional development to influence beliefs. Considerations for design of online professional learning and implications for future research are shared.